2007
DOI: 10.1007/s00426-007-0108-4
|View full text |Cite|
|
Sign up to set email alerts
|

Offline and online automatic number comparison

Abstract: This paper focuses on automatic number processing as instantiated in the size congruity effect. It was recently argued that long-term "associations between individual digits and the attributes 'small' and 'large' create the size congruity effect" (Choplin and Logan 2003, abstract, p. 17). Moreover, these authors proposed the additional assumption that the relevant connections are acquired over a lifetime of experience with numbers. We show that at least one of these assumptions is not true: either the size con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The neural overlap effects found in Fias, Lauwereyns et al (2001) and Lammertyn et al (2002) are specific in the sense that the irrelevant information always consisted of numbers. Spatial information associated with irrelevant numbers is implicit and although it is generally believed that numerical information is automatically processed upon the mere exposure to numbers (Dehaene & Akhavein, 1995; Fias, Reynvoet, & Brysbaert, 2001; Koechlin, Naccache, Block, & Dehaene, 1999; Naccache & Dehaene, 2001; Cohen Kadosh & Henik, 2006; Van Opstal, Moors, Verguts, & Fias, in press) it is possible that this kind of semantic information is more susceptible to contextual modulation than explicit spatial information. In the present study a Simon paradigm was used where stimulus position was used instead of numbers to evoke spatial representations of left and right.…”
Section: The Present Studymentioning
confidence: 99%
“…The neural overlap effects found in Fias, Lauwereyns et al (2001) and Lammertyn et al (2002) are specific in the sense that the irrelevant information always consisted of numbers. Spatial information associated with irrelevant numbers is implicit and although it is generally believed that numerical information is automatically processed upon the mere exposure to numbers (Dehaene & Akhavein, 1995; Fias, Reynvoet, & Brysbaert, 2001; Koechlin, Naccache, Block, & Dehaene, 1999; Naccache & Dehaene, 2001; Cohen Kadosh & Henik, 2006; Van Opstal, Moors, Verguts, & Fias, in press) it is possible that this kind of semantic information is more susceptible to contextual modulation than explicit spatial information. In the present study a Simon paradigm was used where stimulus position was used instead of numbers to evoke spatial representations of left and right.…”
Section: The Present Studymentioning
confidence: 99%
“…Even when instructed to ignore the numerical value, healthy adult subjects show a strong congruity effect (longer reaction times for incongruent trials compared to congruent trials) because the numerical value is processed automatically. This congruity effect, which is termed size congruity effect , has been considered for almost 20 years as a marker of automatic numerical processing (Henik and Tzelgov, 1982; Tzelgov et al, 1992; Schwarz and Heinze, 1998; Schwarz and Ischebeck, 2003; Szucs et al, 2007; Cohen Kadosh et al, 2008b, 2011; Van Opstal et al, 2008b; Gebuis et al, 2009; Rubinsten and Henik, 2009; Santens and Verguts, 2011). It has been shown that those who have better numerical abilities exhibit a greater level of automaticity as reflected by a larger size congruity effect (Girelli et al, 2000; Rubinsten et al, 2002; Rubinsten and Henik, 2005, 2006; Cohen Kadosh et al, 2007b; Mussolin and Noël, 2008).…”
Section: Introductionmentioning
confidence: 99%